Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.3748/wjg.15.3201
|View full text |Cite
|
Sign up to set email alerts
|

What every gastroenterologist needs to know about common anorectal disorders

Abstract: Anorectal complaints are very common and are caused by a variety of mostly benign anorectal disorders. Many anorectal conditions may be successfully treated by primary care physicians in the outpatient setting, but patients tend not to seek medical attention due to embarrassment or fear of cancer. As a result, patients frequently present with advanced disease after experiencing significant decreases in quality of life. A number of patients with anorectal complaints are referred to gastroenterologists. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 89 publications
2
54
0
10
Order By: Relevance
“…The prevalence rate of symptomatic haemorrhoids in the United States is 4.4% of the total adult population. 5 which matches with our findings.…”
supporting
confidence: 93%
“…The prevalence rate of symptomatic haemorrhoids in the United States is 4.4% of the total adult population. 5 which matches with our findings.…”
supporting
confidence: 93%
“…(13) Persistent minor fecal incontinence has been reported in 1.2% to 3.5% of patients; however, this does not appear to be significantly different to the rate of minor fecal incontinence experienced by patients treated with topical GTN. (9) However, in a systematic review carried out by Garg P et al to analyse continence at 2 years or more after lateral internal sphincterotomy for chronic anal fissure, the long term risk of anal incontinence after lateral internal sphincterotomy was found to be quite significant. (14) He had 324 studies screened, 22 (n=4512) were included in the study and he reported an overall continence disturbance rate was 14%.…”
Section: Discussionmentioning
confidence: 99%
“…(8) Lateral internal sphincterotomy is the preferred method of surgery for persons with chronic anal fissures and is generally used when medical therapy has failed. (9) The procedure has been shown to be very effective with 96% of fissures healing at a median of 3 weeks in one trial. (10) It is associated with a lower rate of side effects than older techniques, such as posterior internal sphincterotomy and anoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Rekürrens ve komplikasyonların azaltılabilmesi için preoperatif görüntüleme önemle vurgulanmaktadır [8,9]. MRG temel görüntüleme yöntemidir [10].…”
Section: Görüntüleme Yöntemleriunclassified